A highly sensitive NanoLuc-based protease biosensor for detecting apoptosis and SARS-CoV-2 infection - Masashi Arakawa; Akiho Yoshida; Shinya Okamura; Hirotaka Ebina; Eiji Morita (Scientific Reports, 2023)
Abstract Proteases play critical roles in various biological processes, including apoptosis and viral infection. Several protease biosensors have been developed; however, obtaining a reliable signal from a very low level of endogenous protease activity remains a challenge. In this study, we developed a highly sensitive protease biosensor, named FlipNanoLuc, based on the Oplophorus gracilirostris NanoLuc luciferase. The flipped β-strand was restored by protease activation and cleavage, resulting in the reconstitution of luciferase and enzymatic activity. By making several modifications, such as introducing NanoBiT technology and CL1-PEST1 degradation tag, the FlipNanoLuc-based protease biosensor system achieved more than 500-fold luminescence increase in the corresponding protease-overexpressing cells. We demonstrated that the FlipNanoLuc-based caspase sensor can be utilized for the detection of staurosporine-induced apoptosis with sixfold increase in luminescence. Furthermore, we also demonstrated that the FlipNanoLuc-based coronavirus 3CL-protease sensor can be used to detect human coronavirus OC43 with tenfold increase in luminescence and severe acute respiratory syndrome-coronavirus-2 infections with 20-fold increase in luminescence by introducing the stem-loop 1 sequence to prevent the virus inducing global translational shutdown.